Leptin Elicits LTC4 Synthesis by Eosinophils Mediated by Sequential Two-Step Autocrine Activation of CCR3 and PGD2 Receptors - Amorim, Natália R. T.; Luna-Gomes, Tatiana; Gama-Almeida, Marcos; Souza-Almeida, Glaucia; Canetti, Claudio; Diaz, Bruno L.; Weller, Peter F.; Torres Bozza, Patricia; Maya-Monteiro, Clarissa M.; Bandeira-Melo, Christianne (Frontiers in Immunology, 2018)
Leptin is a cytokine, produced mainly by mature adipocytes, that regulates the central nervous system, mainly to suppress appetite and stimulate energy expenditure. Leptin also regulates the immune response by controlling activation of immunomodulatory cells, including eosinophils. While emerging as immune regulatory cells with roles in adipose tissue homeostasis, eosinophils have a well-established ability to synthesize pro-inflammatory molecules such as lipid mediators, a key event in several inflammatory pathologies. Here, we investigated the impact and mechanisms involved in leptin-driven activation of eicosanoid-synthesizing machinery within eosinophils. Direct in vitro activation of human or mouse eosinophils with leptin elicited synthesis of lipoxygenase as well as cyclooxygenase products. Displaying selectivity, leptin triggered synthesis of LTC4 and PGD2, but not PGE2, in parallel to dose-dependent induction of lipid body/lipid droplets biogenesis. While dependent on PI3K activation, leptin-driven eosinophil activation was also sensitive to pertussis toxin, indicating the involvement of G-protein coupled receptors on leptin effects. Leptin-induced lipid body-driven LTC4 synthesis appeared to be mediated through autocrine activation of G-coupled CCR3 receptors by eosinophil-derived CCL5, inasmuch as leptin was able to trigger rapid CCL5 secretion, and neutralizing anti-RANTES or anti-CCR3 antibodies blocked lipid body assembly and LTC4 synthesis induced by leptin. Remarkably, autocrine activation of PGD2 G-coupled receptors DP1 and DP2 also contributes to leptin-elicited lipid body-driven LTC4 synthesis by eosinophils in a PGD2-dependent fashion. Blockade of leptin-induced PGD2 autocrine/paracrine activity by a specific synthesis inhibitor or DP1 and DP2 receptor antagonists, inhibited both lipid body biogenesis and LTC4 synthesis induced by leptin stimulation within eosinophils. In addition, CCL5-driven CCR3 activation appears to precede PGD2 receptor activation within eosinophils, since neutralizing anti-CCL5 or anti-CCR3 antibodies inhibited leptin-induced PGD2 secretion, while it failed to alter PGD2-induced LTC4 synthesis. Altogether, sequential activation of CCR3 and then PGD2 receptors by autocrine ligands in response to leptin stimulation of eosinophils culminates with eosinophil activation, characterized here by assembly of lipidic cytoplasmic platforms synthesis and secretion of the pleiotropic lipid mediators, PGD2, and LTC4.